2017
DOI: 10.18632/oncotarget.16684
|View full text |Cite
|
Sign up to set email alerts
|

Exosome: emerging biomarker in breast cancer

Abstract: Exosomes are nano-sized membrane vesicles released by a variety of cell types, and are thought to play important roles in intercellular communications. In breast cancer, through horizontal transfer of various bioactive molecules, such as proteins and mRNAs, exosomes are emerging as local and systemic cell-to-cell mediators of oncogenic information and play an important role on cancer progression. This review outlines the current knowledge and concepts concerning the exosomes involvement in breast cancer pathog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
193
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 209 publications
(206 citation statements)
references
References 140 publications
(161 reference statements)
2
193
0
Order By: Relevance
“…Exosomes generated by tumor cells can mediate angiogenesis and the proliferation and immune escape of cancer cells, while dendritic cells‐derived exosomes can induce effective anti‐tumor immune response. Those exosomes‐specific proteins, nucleic acids, lipids, and even some important signaling molecules are expected to be targets in the early diagnosis and treatment of certain diseases . Currently available studies have suggested that exosomes are expected to be novel way of drug administration and gene therapy vectors in cancer, in that exosomes can pass through biological barriers and deliver exosomes‐encapsulated proteins, miRNAs, and so on, between cells .…”
Section: Discussionmentioning
confidence: 99%
“…Exosomes generated by tumor cells can mediate angiogenesis and the proliferation and immune escape of cancer cells, while dendritic cells‐derived exosomes can induce effective anti‐tumor immune response. Those exosomes‐specific proteins, nucleic acids, lipids, and even some important signaling molecules are expected to be targets in the early diagnosis and treatment of certain diseases . Currently available studies have suggested that exosomes are expected to be novel way of drug administration and gene therapy vectors in cancer, in that exosomes can pass through biological barriers and deliver exosomes‐encapsulated proteins, miRNAs, and so on, between cells .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, data have shown that breast cancer cells-derived exosomes cause induction of tumor-promoting factors, like stromal cell-derived factor 1 (SDF-1), VEGF, chemokine ligand 5 (CCL5), and TGF-β in the adipose tissuederived mesenchymal stem cells (ADSCs) and induce the myofibroblastic phenotype via a SMAD-mediated pathway (Cho, Park, Lim, & Lee, 2012). Kosaka et al (2013) (Jia et al, 2017). Fong et al (2015) showed that cancer cells secrete elevated levels of miR-122 into exosomes and also they found that miR-122 can be transferred to normal cells and inhibit glucose uptake by them via downregulating the glycolytic enzyme pyruvate kinase (PKM).…”
Section: Breast Cancermentioning
confidence: 99%
“…It has been shown that exosomes play an important role in cancer cell invasion and metastasis, stem cell stimulation, angiogenesis, apoptosis, interaction with immune system cells, and drug resistance [102,103]. Hannafon et al reported selective encapsulation or elevated enrichment of certain microRNAs in exosomes release in the bloodstream of patients with breast cancer [104], and other studies have reported elevated CEA and CA 15-3 in the exosomes of such patients [103]. Additionally, the presence of ceratin microRNAs in exosomes has been shown to have a strong association with specific subtypes of breast cancer, e.g.…”
Section: Comparison With Other Biomarkersmentioning
confidence: 99%